Synthesis, Characterization and Antimicrobial Activity of Mixed Ligand Complexes of Dioxouranium(VI) with Isatin-3-phenyl Hydrazone. - ABHILASHA, A. (Asian Journal of Chemistry, 2010)
Complexes of dioxouranium(VI) with the Schiff base derived from a heterocyclic amide (isatin) and phenylhydrazine have been synthesized and their physico-chemical properties investigated using elemental analysis, molar conductance, molar mass determination, IR, UV-visible and 1H NMR spectral data. Isatin-3-phenylhydrazone acts as a bidentate chelating agent coordinating through the oxygen and nitrogen atoms of >C=O and >C=N groups, respectively. Various anions such as acetate, lactate, nitrate, perchlorate, sulphate and thiocyanate act as secondary ligands by coordinating to the metal ion. Thermal stability and mechanism of decomposition of a few complexes were determined by TG and DTA techniques. X-ray diffraction study of the acetato complex suggests that it crystallizes in orthorhombie system. The ligand and some of its complexes were screened for their antibacterial and antifungal activities towards Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Cryptococcus neoformans and Candida albicans.